Experimental study on energy transformation and separation characteristic of circulatory flash evaporation. (August 2016) - Zhang, Yousen; Wang, Jinshi; Yan, Junjie; Chong, Daotong; Liu, Jiping
Highlights: A circulatory flash evaporation system was designed and built. Flash evaporation efficiency and steam-carrying ratio was proposed. Variation of flash evaporation efficiency versus experimental parameters was revealed. Variation of steam-carrying ratio versus experimental parameters was illustrated. Abstract: Flash evaporation efficiency and steam-carrying ratio under low superheat were introduced to investigate energy transformation and separation characteristic of circulatory flash evaporation in present paper. Experiments were carried out with flow rates of 400, 600, 800, 1000, 1200 L·h −1, initial water film heights ranging from 100 to 300 mm, initial water film concentration of 0, 5%, 10% and at pressures of 7.4, 12.3, 19.9, 31.2, 47.4 kPa, respectively. Results indicated that flash evaporation efficiency increased with increasing flow rate and flash chamber pressure, but decreased with increasing initial water film height and initial water film concentration. Since upward steam carries the droplets out of the flash chamber, the value of experimental flash vapor mass was larger than the theoretical one which not considering the steam-carrying effect. Steam-carrying ratio under low superheat decreased with increasing of superheat and mass flow rate, but increased with increasing water film height. Moreover, there was a peak value in steam-carrying ratio curve for static flash evaporation while the steam-carrying ratio for circulatory flash evaporation decreased monotonically.